Customer requirement-driven design method and computer-aided design system for supporting service innovation conceptualization handling. (August 2020) - Lee, Ching-Hung; Chen, Chun-Hsien; Lee, Yu-Chi
Abstract: How to create value to meet customers' requirements by effectively using advanced digital technology (DT) for digital transformation is an implementation challenge for new and future scenarios of current contexts. Valid digital transformation issues need to be considered to deliver novel values with sustainability concerns. Attempting to effectively achieve a successful service system design in an industrial context, a holistic customer requirement-driven service design method with abductive logic was proposed to drive self-service productivity enhancement. Laddering theory, ontology-based design knowledge hierarchy (DKH), theory of inventive problem solving (TRIZ) and quality function deployment (QFD) technique are adopted in terms of effective design knowledge handling in innovation conceptualization with a traceable path and abductive logic linking from customer concerns, business context and technology digitization. Then, a comprehensive case study of an empirical smart meal-ordering service system for the digital transformation of canteen processes was illustrated to verify this approach.